Development and validation of teacher curriculum paradigm and actual curriculum development practice instruments for Malaysian teacher curriculum paradigm model - Liew, Yon Foi (2012)
The success of the educational reform for a nation is strongly dependent on teachers’ actual curriculum development practice, which they enact in the real teacher-student interaction context. Therefore, the teachers’ enactment of the actual curriculum development practice is crucial to determine the success or the failure of the education because it gives the direct impact towards student learning. Consequently, the growing educational interest in identifying and assessing the variable that can govern teachers’ actual curriculum development practice and the variable of actual curriculum development practice are significant and compelling. Correspondingly, the endeavours to develop and validate the two instruments to measure the teacher curriculum paradigm (TCP) and the actual curriculum development practice (ACDP) were aspired by this study. Sequentially, the positive impact of TCP to ACDP was hypothesised and tested empirically through the teacher curriculum paradigm model (TCP-Mo). This study was divided into three phases. Phase one included the systematic instrument development processes and the attaining of the content validity and reliability of the instruments. The content validity was acquired while the full agreement of the three subject experts had been granted. Both instruments met the item discriminant criteria (the corrected item-total correlation values more than .30) and high reliability index across the three times instrument testing (α > .93). The adequacy of the dual scale format in developing the Scale A and Scale B by employing a single table of content specification was identified by the bivariate correlation testing (r <.70) and the pairedsamples t-test. Phase two involved the single-group analysis with Structural Equation Modelling approach to test for the factorial validity of the measurement models and the structural model for the TCP-Mo. The theoretical structure of the latent variables: TB, TV, ACDP and TCP was identified with the Confirmatory Factor Analysis. The first-order factors: TB, TV and ACDP had been identified were unidimensional construct while the TCP was a second-order factor significantly comprised by two first-order factors: TB and TV. Both instruments had attained the construct validity and reliability to denote that they are the valid and practical instruments. Sequentially, the full structural modelling testing was executed and the findings have signified the validity of the causal structure of TCPMo to support the TCP concept. Eventually, the equivalence testing of the TCP-Mo across three groups of teacher, who embraced the different types of paradigm, was examined through the multiple-group analysis in phase three. The TCP-Mo achieved the fifth degree of cross validation testing to denote that the TCP-Mo was invariant across teachers of three different types of paradigm. Besides, the six research hypotheses were tested to support the validity of the instruments and the structural model. The validity and the stability of the instruments and the generalisability of TCP-Mo have been cogently justified by the findings of this study. Assertively, the outcomes of this study have significantly added insights into psychometric field of the instruments in measuring TCP and ACDP, and the body of knowledge regarding the TCP concept, which can govern teachers’ ACDP to improve student leaning and uphold the success of the educational vision for a nation.